ENHANCING EDUCATIONAL SELF-CONFIDENCE THROUGH A GUIDANCE ACTIVITY PACKAGE BASED ON THE FIVE BALA FOR UPPER PRIMARY STUDENTS AT WAT SAMUHARAT BAMRUNG SCHOOL IN PATHUM THANI PROVINCE - Kleangkhow, Vasawat; Aphipanyo, PhrapaladSoravit; Mererk, Sayyud (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aims to: 1) create a set of guidance activities based on the Five Powers (Bala 5) Principles to enhance academic self-confidence of upper primary school students at Wat Samuharat Bamrung School, Pathum Thani Province; and 2) study the effects of using the guidance activities set based on the Five Powers (Bala 5) in enhancing academic self-confidence of upper elementary school students at Wat Samuharat Bamrung School, Pathum Thani Province. This research utilized a quasi-experimental research design to evaluate the impact of a guidance activity set based on the Five Powers (Bala 5) and a questionnaire to measure the dependent variable before and after the use of the guidance activities based on the Five Power (Bala 5) with a sample group of 30 Grade 5 students at Wat Samuhrat Bamrung School, selected through simple random sampling to obtain the most in-depth and useful information from limited resources. Data were analyzed using research statistics: mean and standard deviation. The research findings revealed that: 1) The guidance activity set developed consisted of 10 sessions, each lasting 50 minutes. The activities were designed to systematically promote the development of educational self-confidence through a learning process conducive to developing students' educational self-confidence. This developed activity set can be effectively applied in the school context to enhance students' educational self-confidence. 2) After using with students participating in guidance activities based on the Five Powers (Bala 5), the sample group of students who participated in the guidance activities based on the Five Powers (Bala 5), showed a statistically significant improvement in their scores on the educational self-confidence test after the experiment compared to before the experiment at the 0.05 level.